The Measurement of Organizational Culture: Cross-country Perspective. Organisatsioonikultuuri mõõtmine: kultuuriülene perspektiiv. - Karma, Kadri; Vadi, Maaja (Estonian Discussions on Economic Policy, 2016)
This paper contributes to the research on organizational culture (OC) from a crosscountry perspective. From the economic point of view we see that society today has led us to increasing international cooperation and globalization. Despite the opening of economic borders there are still limits to consider when operating across national boundaries. One of those limits can be associated with culture – the way things are commonly understood and accepted in different national entities. This can be of special importance for small countries, as they need to adjust to their larger counterparts in order to be economically competitive. Research focuses on different aspects when studying OC, but it is generally agreed that task orientation and interpersonal relationships become important dimensions when we analyze this phenomenon. In order to understand OC and to measure it in cross cultural settings, a universal measurement tool is needed; however, drafting such a tool has for some time been a sticky task. In this paper the measurement invariance of the Organizational Culture Questionnaire (Vadi et al. 2002) is examined by comparing the data from seven countries representing Eastern and Western Europe, Russia, and China. This sample covers both small and large countries. A confirmative factor analysis was used as a means to test measurement invariance across the selected samples. In addition, Multidimensional Scaling technique was applied to provide a visual representation of the data. An analysis was carried out using the statistical software SPSS/AMOS 17.0. The results indicate that task orientation can be found as a common dimension whereas relationship orientation seems to hold a diverse meaning across countries. Instead of relationship orientation, a dimension reflecting negative employee emotions towards the organization was detected. It also turned out that the strength of the relationship between the obtained subscales shows interesting variation across countries. These findings potentially allow us to better understand and lead international collaboration between countries and organizations.